Contemporary Volunteering in the Formation of Prosocial Behaviour of a Person - P. A. Kislyakov; E. A. Shmeleva; O. Gowin (Russian State Vocational Pedagogical University, 2019)
Introduction. In modern society, there is a growing demand for the spread of prosocial practices, among which the leading role is given to the volunteer movement. In this regard, the actual pedagogical task is the education of a prosocial person - a member of the public, whose activity is focused on the gratuitous societal service and is resulted from altruistic motives. Students are potential members, who can be involved in such activities. Student community is considered as a special social group, which is characterised by the highest degree of civic activity, the desire for self-organisation and self-realisation in various spheres of life.The aims of the research presented in the article are to identify and analyse the attitude of youth to different types of volunteering; to justify the need for support and development of the volunteer movement as one of the main conditions for the safe and sustainable existence of society.Methodology and research methods. The research was based on personal and socio-cognitive approaches to the process of education of the new generation, as well as on the key provisions of the theory of social security. The methods of focus group research, interviews, questionnaires and Internet surveys were employed as tools for information collection. The data obtained were generalised and processed using qualitative and quantitative methods of analysis, including content analysis, percentage analysis, correlation analysis through Pearson coefficient and factor analysis (principal component method, varimax rotation). The calculations were made with the use of the statistical software package SPPS 17.Results and scientific novelty. The phenomenon of volunteering is considered as an important factor of social solidarity and social trust and as a form of safe prosocial behaviour of the individual. Based on the responses of respondents, who took part in the surveys, typical ideas about the motivation of the volunteer, his or her personal qualities and conditions of familiarising with various volunteer practices are identified, studied and generalised. The authors built up a psychological profile of a modern young man, capable of voluntary selfless acts for the benefit of others. Three groups of factors of formation of prosocial behaviour in the youth environment are allocated: social and ecological, educational and civil, cultural and religious. The types of volunteer activities are ranked according to the degree of their influence on the social well-being of the people around them in society according to the potential of gratuitous benefit for other people. From the perspective of the Russian Government and student community, it was revealed that there are some differences in assessing the potential of volunteerism in terms of the importance of selfless actions that contribute to human well-being in society. Conflicting priorities defined by the survey participants, and, the range of activities proclaimed in the Concept of development of volunteerism (volunteering) in the Russian Federation until 2025, can be connected with students' insufficient awareness on voluntary projects or can be indicative for the risks of socialisation of young people.Practical significance. The present research, on the one hand, enriches the field of knowledge about the essence of safe prosocial behaviour of the individual and, on the other hand, this study has a practice-oriented significance, as it can serve as a basis for the development of methods of psychological and pedagogical impact on the development of human readiness for prosocial behaviour, implemented through voluntary activity.